2014
DOI: 10.1007/s00192-013-2295-4
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary symptoms and their effects on quality of life in women with uterine myomas

Abstract: Urinary tract dysfunction is associated with anterior myomas, increasing in association with myoma size, and significantly affects QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Many conditions of the female reproductive tract can cause or worsen urinary symptoms. For example, women with a diagnosis of uterine fibroids (leiomyomas) report a high prevalence of urinary symptoms of 73‐76% . The exact relationship between fibroids and the bladder is poorly understood .…”
Section: Introductionmentioning
confidence: 99%
“…Many conditions of the female reproductive tract can cause or worsen urinary symptoms. For example, women with a diagnosis of uterine fibroids (leiomyomas) report a high prevalence of urinary symptoms of 73‐76% . The exact relationship between fibroids and the bladder is poorly understood .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, women had more voiding dysfunction when the largest fibroids were anterior as compared to other locations. Ekin et al in a prospective study of 145 women with fibroids showed that fibroid size and anterior position were associated with worse LUTS [7]. In contrast, a recent study of 85 women, whilst confirming a positive association between fibroid volume and LUTS scores, did not find any significant impact of fibroid position [16].…”
Section: Fibroid Size and Positionmentioning
confidence: 88%
“…The most common LUTS in women with uterine fibroids are urinary urgency, increased daytime frequency and nocturia [6]. Urgency urinary incontinence (UUI), stress urinary incontinence (SUI) and voiding difficulties have also been shown to be more common in women with fibroids [7,8]. Obstructive uropathy of the upper urinary tract and subsequent recurrent urinary tract infections and renal damage might also occur in the case of large fibroid uteri [9].…”
Section: Introductionmentioning
confidence: 98%
“…When asked about their symptoms in the last 12 months, over half (50.6%) of women with myoma uteri reported a negative impact on their daily life [2] . Moreover, women with myoma uteri have significantly higher frequency of genitourinary symptoms including stress urinary incontinence, mixed urinary incontinence, urgency, daytime frequency, and dyspareunia [3] .…”
Section: Introductionmentioning
confidence: 99%